Penegakan Hukum Pidana terhadap Penyalahgunaan Ganja oleh Pelaku yang Mengalami Gangguan Jiwa (Studi Putusan No. 1/Pid.Sus/2022/PT SMG) - Wijaya, Adhitya Katon; Rochmani, Rochmani (Wajah Hukum, 2025)
The author’s research for the thesis entitled “Criminal Law Enforcement Against Cannabis Abuse by Offenders with Mental Disorders (Case Study of Decision No. 1/Pid.Sus/2022/PT SMG)” focuses on examining how criminal law is applied to offenders who abuse cannabis while suffering from mental disorders, as well as reviewing the judge’s considerations in delivering criminal verdicts. This research employs a library research method, legal document collection, and descriptive qualitative data analysis. The data sources include official court decisions, statutory regulations, and relevant legal literature, which are used to provide a descriptive account of the application of criminal law to cannabis abuse committed by offenders with mental disorders. The findings reveal that the implementation of Article 44 of the Indonesian Criminal Code (KUHP) in such cases remains inconsistent. Law enforcement tends to prioritize repressive punishment over rehabilitative measures, even when there is strong medical and psychological evidence supporting the offender’s mental disorder. This situation indicates the need for policy and procedural reforms to ensure that the human rights and mental health care needs of the offenders are adequately protected. Furthermore, the study offers deeper insights into the importance of a legal approach that is not solely repressive but also takes into account the psychological condition and human rights of the offenders.